Antioxidant and anti–inflammatory effects of Helichrysum plicatum DC. subsp. plicatum extract in an experimental model of acute urolithiasis - Selvinaz Yakan; Kıvılcım Eren Erdoğan; Yusuf Kenan Dağlıoğlu; Tuba Aydın; Ahmet Çakır (Revista Científica)
This study aimed to view the antioxidant and anti–inflammatory properties of Helichrysum plicatum DC. subsp. plicatum (HP) methanol extract on the urinary tract using an experimentally induced urolithiasis (U) model. The study included four groups: Group 1 was given a standard diet, Group 2 was given a diet added with HP, Group 3 was given a standard diet with induced urolithiasis, and Group 4 received an HP–supplemented diet with induced urolithiasis. Rats in Groups 2 and 4 were administered 500 mg·kg-1·day-1 of HP via gavage feeding for 21 days. Urolithiasis was induced in Groups 3 and 4 by administering 1% ethylene glycol and 1% ammonium chloride in their swig water for 21 days to create a calcium oxalate (CaOx) urolithiasis model. The study analyzed plasma concentrations of thiobarbituric acid reactive substances (TBARS), an indicator of serum oxidative stress (OS), HP, and HP levels. Additionally, oxalate (Ox), urea, calcium, and creatinine clearance levels were measured in both blood and urine, and routine histological evaluations were conducted. The results indicated important higher concentrations of HP in the groups given HP (P<0.001), while plasma TBARS concentrations were lower in Group 4 compared to Group 3 (P=0.001). The findings suggest that HP reduces OS by lowering plasma TBARS levels induced by CaOx, due to its antioxidant and anti–inflammatory properties. Furthermore, the measured biochemical measurements supported the anti–urolithiasis effects of HP. In results, this study supports the hypothesis that HP’s antioxidative and anti–inflammatory properties help prevent OS, which is a factor in stone formation, thereby preventing acute renal damage and stone formation.